Penegakan Hukum Pidana terhadap Penyebaran Konten Perjudian di Ruang Digital - Berlian Adinda Syafira; Fristia Berdian Tamza; Rinaldy Amrullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid development of information and communication technology has led to the emergence of various forms of digital-based crimes, including the dissemination of electronic information containing online gambling content through social media. This situation poses challenges for criminal law enforcement, as the parties involved are not limited to gambling operators but also include individuals who promote and facilitate access to online gambling platforms. This study aims to examine criminal liability for perpetrators who disseminate electronic information containing gambling content and to analyze judicial considerations in sentencing, referring to the Decision of the Tanjung Karang District Court Number 823/Pid.Sus/2024/PN Tjk. The method used is normative juridical research with statutory, conceptual, and case approaches. Data were collected through literature studies of relevant regulations, criminal law doctrines, and court decisions, and then analyzed using a descriptive qualitative method. The results show that the elements of criminal liability are fulfilled, including the existence of a criminal act, intent, capacity to be responsible, and the absence of grounds that eliminate criminal liability. Furthermore, the panel of judges’ considerations reflect a balanced assessment between juridical and non-juridical aspects, resulting in a decision that embodies legal certainty, justice, and utility. This study is expected to contribute to the development of criminal law, particularly in addressing online gambling crimes in the digital space.